Impact of Financial Revenues and Net Financial Payouts on Investment Efficiency: Evidence from U.S. Non-Financial Firms - Nasir, Abdul Majid; Ahmed, Riaz; Muhammad Ayyoub; Muhammad, Mushtaq (iRASD Journal of Economics, 2024)
This study investigates the effects of financial revenues and net financial payouts on investment efficiency among U.S. non-financial corporations with a particular emphasis on underinvesting firms. This study utilized 20 years of panel data of U.S. non-financial corporations from 1999 to 2018 and deployed the cumulant estimator to investigate the study objectives. We found that financial revenues reduce investment efficiency. Financial revenues also increase underinvestment. This reducing effect of financial revenues on investment efficiency is more prominent in financially unconstrained firms when compared to financially constrained firms. In contrast, net financial payouts enhance investment efficiency and decrease underinvestment. The positive relationship of net financial payouts with investment efficiency is more compelling when considering the composite proxy of net financial payouts instead of net shares repurchases and net equity payouts. The relationship is also stronger during uncertainty. These results are robust to an alternative estimation method. This study's implications are important to firms, investors and governments, as investment efficiency is an important factor that enhances corporate long-term growth. Firms and investors looking to improve investment efficiency may reinvest the financial revenues in real assets to reduce underinvestment. They may also consider the net financial payouts instead of financial payouts when determining the real investment behavior.